Biomechanical Research on Special Ability of Long Jump Take-Off Muscle Based on Multisource Information Fusion - Yue Ren; Bingquan Luo; Jun Chu (Applied Bionics and Biomechanics)
For athletes of different sports, their muscle activities in different sports will show different special characteristics according to different sports. The purpose of this paper is to study the technology of multi-information fusion and to study the athletes of the long jump competition. The relevant research on the muscle specific ability test methods of the athletes in the long jump competition is of great significance to the study of the long jump. This paper proposes a long jumper’s special muscle ability experiment, using the now very popular multi-information fusion technology, to conduct in-depth research on the biomechanics of the long jumper’s special ability of the take-off muscle, which can provide an effective scientific basis for the special ability level and special strength of the long jumper’s take-off sports. The results of the study show that the hip joint of the take-off leg produces greater hip extensor torque during the take-off action of long jump, and the active contraction ability of the knee flexor group is very important for taking off and avoiding damage to the posterior femoral muscle group. The change range of the pressure center is between 51.26% and 74.35%, which has great application value in actual training.